2003
DOI: 10.1590/s0100-879x2003000500016
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of male adult rats submitted to forced swimming stress

Abstract: We investigated whether stress interferes with fertility during adulthood. Male Wistar rats (weighing 220 g in the beginning of the experiment) were forced to swim for 3 min in water at 32ºC daily for 15 days. Stress was assessed by the hot-plate test after the last stressing session. To assess fertility, control and stressed males (N = 15 per group) were mated with sexually mature normal females. Males were sacrificed after copulation. Stress caused by forced swimming was demonstrated by a significant increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 19 publications
3
35
0
2
Order By: Relevance
“…In comparison with the group I; stress produced an extreme significant reduction in sperm count in the all groups when compared with the corresponding control group of animals. In comparison with the stress group (group II), the Intermediate dose of Vit C significant improved & high dose of Vit C very significantly improved in sperm count [23].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In comparison with the group I; stress produced an extreme significant reduction in sperm count in the all groups when compared with the corresponding control group of animals. In comparison with the stress group (group II), the Intermediate dose of Vit C significant improved & high dose of Vit C very significantly improved in sperm count [23].…”
Section: Discussionmentioning
confidence: 80%
“…The observed weight loss may be due to reduced sex hormones [22,23]. In comparison with group II; the group V, VI very significantly (p<0.005) recovered testicular weight.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Exercise is known to cause some testicular impairment (Manna et al 2003;Manna et al 2004;Hackney 2008;Jana et al 2008). Mingoti et al (2003) observed that high-intensity swimming stress caused a significant reduction in the number of spermatids in seminiferous tubules of Wistar rats. So, the reduction in the quantity of round spermatids, preleptotene and pachytene spermatocytes, the loss of SC support capacity and efficiency with the increase of swimming exercise load could be related to the increase of stress caused by load increase.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction in the basal and total testosterone level was observed after intensive endurance exercise in the humans, which could possibly lead to the disruption of testosterone dependent processes (Manna et al 2003;Hackney 2008;Jana et al 2008). Also, intensive swimming exercise has been linked to a vast range of impairments regarding the male fertility, such as reduced spermatic production (Mingoti et al 2003), reduced somatic index of the testes, epididymis, prostate and seminal vesicle (Manna et al 2003), reduced number of preleptotine spermatocytes, midpachytene spermatocytes and stage 7 spermatids (Manna et al 2003;Jana et al 2008), and reduced epididymal sperm count (Jana et al 2008). As observed for the increased colon cancer susceptibility, the damages caused to male fertility by the exercise appear to be associated with an increase in oxidative stress (Manna et al 2003;Manna et al 2004).…”
Section: Introductionmentioning
confidence: 99%